Foreign Direct Investment and Structural Reforms : Evidence from Eastern Europe and Latin America - Kinoshita, Yuko.; Campos, Nauro (Washington, D.C. : International Monetary Fund, 2008)
This paper investigates the role of structural reforms -financial reforms, trade liberalization, and privatization- as determinants of FDI inflows based on newly constructed dataset on structural reforms for 19 Latin American and 25 Eastern European countries between 1989 and 2004. Our main finding is a strong empirical relationship from reforms to FDI, in particular, from financial liberalization and privatization. These results are robust to different measures of reforms, split samples, and potential endogeneity and omitted variables biases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet